2017
DOI: 10.18632/oncotarget.19208
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion and mortality in myocardial infarction: an updated meta-analysis

Abstract: Background Several observational and preclinical studies have shown that blood transfusion may modify the mortality of patients with myocardial infarction (MI). The aim of this meta-analysis is to evaluate the recent evidence on the effectiveness of blood transfusion for all-cause mortality in patients with MI. Materials and Methods PUBMED, EMBASE and the Cochrane central register of controlled trials were searched up to June 2016 by two independent investigators. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Numerous studies of critically ill adults and children have found an association between RBC transfusions and increased mortality and morbidity (1)(2)(3)(4). Although the storage lesion has been well documented for some time and our understanding of the mechanisms involved have increased substantially over the last several years, its role in disease and the clinical consequences remain to be determined (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies of critically ill adults and children have found an association between RBC transfusions and increased mortality and morbidity (1)(2)(3)(4). Although the storage lesion has been well documented for some time and our understanding of the mechanisms involved have increased substantially over the last several years, its role in disease and the clinical consequences remain to be determined (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cardiac disease are transfused at higher hemoglobin thresholds than those without cardiac disease, and the management of cyanotic congenital heart disease often prompts practitioners to target even higher hemoglobin levels. RBC transfusions in cardiac patients are associated with adverse outcomes, including following the Norwood procedure (NP) for palliation of the hypoplastic left heart syndrome (HLHS) (1–4). There is increasing evidence that transfusion of stored RBCs reduces nitric oxide (NO) bioavailability, which may play a role in influencing the postoperative course and clinical outcomes (5–7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, accumulating evidence indicates that anemia engenders outcomes such as increased stroke [9], heart failure [33], hospitalization [25], and mortality [34], all of which impose a severe burden on healthcare systems. Furthermore, anemia is associated with increased iron overload, increased chances of viral infection [35], and increased risks of myocardial infarction [36]. We also analyzed other known conventional risk factors, such as hyperlipidemia and atrial fibrillation, that affect the development of stroke; the hazard ratio was slightly different to other investigations [9].…”
Section: Discussionmentioning
confidence: 99%
“…Zhong and Rao ( 18 ) studied and showed that after the treatment of ischemic cardiomyopathy with CSC transplantation therapy, the migration and proliferation capabilities of CSCs are superior, there are many new cells and blood vessels in the MI region, and cardiac function recovery is better. ILK can regulate intracellular signaling pathways and transmit extracellular signals into cells, thereby promoting cell survival, reducing apoptosis and promoting cell proliferation and differentiation ( 3 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%